Evaluation of properties on performance and emission to turbocharged SI engine using fusel oil blend with gasoline - S. M., Rosdi; R., Mamat; Azri, Alias; Sudhakar, K.; I. M., Yusri (IOP Publishing, 2019)
Biofuel has the potential to be used as an alternative fuel compared to petroleum gasoline for the purpose increase performance and reducing emissions. The objective of the study is to evaluate performance and emission on properties of 10–30% fusel oil blends with pure gasoline (Ron 95) at 3000 rpm. In this experiment, three fuels were designed from fusel oil to test engine performance and emission. The haltech ECU was an escalation to set ignition, injection timing and injection mass when using fusel oil blends to reach stoichiometric level. In this study, pure gasoline was set as a reference. The experiments were conducted on 1.8L turbocharged 4-cylinder, spark ignition engine, port injection and coupled with 100 kW eddy current dynamometer. During engine testing, the throttle position was applied to 10–40%. As a result, averaged BMEP increase at 11.9%, 17.8% and 21.3% for F10, F20 and F30 respectively compared to gasoline. The VE and BSFC averaged increased 8.3% and 6.17% compared to pure gasoline for 10–40% engine load. The emissions for CO and HC on these observations increased while the NOx decreased when fusel oil blends were utilized. The recommendation used in study is low proportion blends to assess different properties for engine test.